POLYTOMOUS QUANTAL RESPONSE OF CROCIDOLOMIA PAVONANA (F.) (LEPIDOPTERA: PYRALIDAE) TO EXTRACTS OF AGLAIA SPP. AND DYSOXYLUM SPP. (MELIACEAE) - Djoko Prijono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
Polytomous Quantal Response of Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae) to Extracts of Aglaia spp. and Dysoxylum spp. (Meliaceae). This work was done to study the polytomous binary response of the cabbage head caterpillar Crocidolomia pavonana (F.) to extracts of two species each of Aglaia and Dysoxylum (Meliaceae). Second-instar larvae C. pavonana were fed extract-treated broccoli leaves for 2 days and then the surviving larvae were maintained on untreated leaves until pupation. Relationship between extract concentration and the number of dead larvae in different instars was analyzed using polytomous quantal response analysis based on the conditional logit model. The results showed that twig extract of Dysoxylum acutangulum and seed extract of D. mollissimum possessed strong insect growth regulating activity against C. pavonana larvae as reflected by highly significant responses in the later insect life stages after the feeding treatment was removed, including the significant occurrence of malformed pupae. On the contrary, the feeding treatment with twig extract of Aglaia odorata and seed extract of A. odoratissima resulted in highly significant responses only in the treated larval instar, and after the feeding treatment was removed, responses in the later life stages were insignificant or much less significant. Overall, the above results suggest that Dysoxylum extracts interfered with hormonally-controlled insect development and metamorphosis, whereas the activity of Aglaia extracts was more insecticidal rather than insect growth regulating.